The sacred gaze : religious visual culture in theory and practice - Morgan, David, 1957- (University of California Press, 2005)
"Sacred gaze" denotes any way of seeing that invests its object - an image, a person, a time, a place - with spiritual significance. Drawing from many different fields, David Morgan investigates key aspects of vision and imagery in a variety of religious traditions. His lively, innovative book explores how viewers absorb and process religious imagery and how their experience contributes to the social, intellectual, and perceptual construction of reality. Ranging widely from thirteenth-century Japan and eighteenth-century Tibet to contemporary America, Thailand, and Africa, The Sacred Gaze disc